Recovery from Severe Mistletoe Infection After Heat- and Drought-Induced Mistletoe Death - Griebel, Anne; Metzen, Daniel; Pendall, Elise; Nolan, Rachael H.; Clarke, Hamish; Renchon, Alexandre A.; Boer, Matthias M. (Ecosystems (New York), 2022)
Mistletoes are emerging as important co-contributors to tree mortality across terrestrial ecosystems, particularly when infected trees are stressed by water limitations during drought. While the mechanistic effects of mistletoe infection on host physiology are reasonably well understood, quantifying the effects of mistletoe infection on stand productivity, canopy turnover and ecosystem structure remains challenging. Moreover, the potential devastating effect of mistletoe infection on host survival has distracted from the challenges that mistletoe populations are facing when increasing drought and heat stress threaten their survival in healthy populations. We coupled intensive observations of mistletoe population dynamics with measurements of host tree stem growth, canopy turnover and stand structure in a severely infected temperate eucalypt woodland to monitor how mistletoe infection alters aboveground biomass distribution and to assess ecosystem recovery from severe mistletoe infection during and after a three-year drought. We show that severe mistletoe infection reduces live standing biomass and canopy volume, with mistletoe leaves contributing up to 43% to total stand litter fall. We further identified that a mistletoe:host leaf area ratio above 60% significantly reduced basal area growth, which provides a threshold for productivity losses due to mistletoe infection in eucalypts. Yet, concurrent increases in basal area and the thickening of canopy volume indicate that host trees recover rapidly after the three-year drought combined with record summer heat nearly extinguished the mistletoe population. How common, or how widespread such dynamic changes in mistletoe population dynamics are within Australian or global ecosystems remains subject to further exploration.